HIGH RISK PREGNANCY DETECTION USING TELEHEALTH-BASED SCREENING - Fatmawati Fatmawati; Yulia Silvani; Mustika Dewi; Ningrum Paramita Sari; Rahma Dian Hanifarizani; Anin Indriani; Rahma Ega Prospera Haryunita; Berliana Maduratna Irawati (Caring : Jurnal Pengabdian Masyarakat, 2021)
High-risk pregnancy is a pregnancy that is likely to cause harm or complications to the mother and fetus. The high maternal mortality rate (MMR) is one of the indicators in determining the degree of public health. Early detection in pregnancy can be used as an effort to increase mother's knowledge about her pregnancy and can facilitate decision making in management. During the COVID-19 pandemic that has hit Indonesia since March 2020, it has caused changes in various aspects of life, especially having a significant impact on the public health aspect. Given the high rate of disease transmission, the use of telehealth technology can be an effective and efficient way to deal with the spread of the virus. Telehealth is one solution to overcome the problem of access to health, with telehealth it can perform screening to detect high-risk pregnancies early so that pregnant women can get continuous monitoring. The purpose of this activity is to conduct and determine the effectiveness of telehealth-based high-risk detection in pregnant women. The method of activity is in the form of community service through webinars and screenings which are carried out within 6 months online. The result of the activity is an increase in the knowledge of webinar respondents with an average pre-test value of 120 and a post-test 157 out of a total of 200. Based on the results of screening using the SIBIDAN application, from 25 pregnant women in trimesters 1,2, and 3 who became respondents, the results were 52%, low-risk group, 32% high-risk group, and 16% very high-risk group. Therefore, further assistance, monitoring, and referral are needed to minimize pregnancy complications.